2009
DOI: 10.1007/s00018-009-9001-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hypoxia-inducible factor-1 regulates human histidine decarboxylase expression

Abstract: Histidine decarboxylase (HDC) catalyzes the formation of histamine from histidine. Histamine has various effects in physiological and pathological reactions, such as inflammation, cell growth, and neuro-transmission. We investigated the role of hypoxia-inducible factor (HIF)-1 on hypoxia-induced HDC expression in human mast cell line, HMC-1 cells and mouse bone marrow-derived mast cells (BMMCs). Hypoxia significantly increased histamine production. HDC expression and activity were induced by hypoxia. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 32 publications
0
36
1
Order By: Relevance
“…It is supposed that hypoxia might be an important factor to induce muscle fatigue. Indeed, a recent report has demonstrated that hypoxia-inducible factor-1 (HIF) has an HDC-inducing activity, 34) suggesting that the less PW-endurance of H1-KO mice might be due to a larger production of HIF due to hypoxia. Collectively, the results obtained by the present study may also support the idea that (i) histamine or HDC induction may be important to reduce exercise-induced fatigue as a protective mechanism, and (ii) mice with a lower PW-endurance may need more HDC induction against hypoxia due to PW.…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that hypoxia might be an important factor to induce muscle fatigue. Indeed, a recent report has demonstrated that hypoxia-inducible factor-1 (HIF) has an HDC-inducing activity, 34) suggesting that the less PW-endurance of H1-KO mice might be due to a larger production of HIF due to hypoxia. Collectively, the results obtained by the present study may also support the idea that (i) histamine or HDC induction may be important to reduce exercise-induced fatigue as a protective mechanism, and (ii) mice with a lower PW-endurance may need more HDC induction against hypoxia due to PW.…”
Section: Discussionmentioning
confidence: 99%
“…AR is characterized by a two-phase allergic reaction. In the early-phase inflammatory response, the allergen-IgE dependent activation of mast cells and basophils results in the production of pharmacologically active mediators such as histamine, prostaglandins, leukotrienes, and cytokines which produce sneezing, rhinorrhea, and itching (Jeong et al, 2009). The late-phase of AR shows accumulations of mast cells, eosinophils, and basophils in the epithelium and an accumulation of eosinophils in the deeper lamina propria (Fuentes-Beltrán et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…AR is characterized by a two-phase allergic reaction. In the early-phase inflammatory response, allergenIgE-dependent activation of mast cells and basophils results in the production of pharmacologically active mediators, such as histamine, prostaglandins, leukotrienes, and cytokines that produce sneezing, rhinorrhea, and itching (Jeong et al, 2009). The late-phase of AR shows accumulations of mast cells, eosinophils, and basophils in the epithelium and an accumulation of eosinophils in the deeper lamina propria (Fuentes-Beltrán et al, 2009).…”
Section: Discussionmentioning
confidence: 99%